Central rather than brachial pressures are stronger predictors of cardiovascular outcomes: A longitudinal prospective study in a Chinese population. Issue 4 (9th March 2020) - Dong, Ying; Jiang, Linlin; Wang, Xin; Chen, Zuo; Zhang, Linfeng; Zhang, Zugui; Zheng, Congyi; Kang, Yuting; Wang, Zengwu; Cao, Huiqing; Wang, Xiaoxia; Fang, Tian; et al.
Abstract: The purpose of this study was to assess the association of blood pressure (BP) measurements with the risk of cardiovascular disease (CVD) and examine whether central systolic BP (CSBP) predicts CVD better than brachial BP measurements (SBP and pulse pressure [PP]). Based on a cross‐sectional study conducted in 2009‐2010 with follow‐up in 2016‐2017 among 35‐ to 64‐year‐old subjects in China, we evaluated the performance of non‐invasively predicted CSBP over brachial BP measurements on the first CVD events. Each BP measurement, individually and jointly with another BP measurement, was entered into the multivariate Cox proportional‐hazards models, to examine the predictability of central and brachial BP measurements. Mean age of participants (n = 8710) was 50.1 years at baseline. After a median follow‐up of 6.36 years, 187 CVD events occurred. CSBP was a stronger predictor for CVD than brachial BP measurements (CSBP, 1‐standard deviation increment HR = 1.49, 95%CI: 1.31‐1.70). With CSBP and SBP entering into models jointly, the HR for CSBP and SBP was 1.28 (1.04‐1.58) and 1.22 (0.98‐1.50), respectively. With CSBP and PP entering into models jointly, the HR for CSBP and PP was 1.51 (1.28‐1.78) and 0.98 (0.83‐1.15), respectively. For subgroup analysis, the association of CSBP with CVD was stronger than brachial BP measurements in women, those with hypertension and obesity. In the middle‐aged Chinese population, noninvasively estimated CSBP may offer advantages over brachial BP measurements to predict CVD events, especially for participants with higher risk. These findings suggest prospective assessment of CSBP as a prevention and treatment target in further trials.